History of housing policy’s formation and development in Ukraine - Avramova, Olga; Oksana, Homotiuk; Lesia, Bilovus; Mysyk, Volodymyr; Zakhozhai, Zoreslava (Edelweiss Applied Science and Technology, 2024)
The purpose of this article is to reveal specific features of the history of the formation and development of housing policy in Ukraine from the ХІХ century to the present time has been researched. Obtaining research results became possible due to the application of general philosophical and special methods of scientific cognition. The factors that influenced the development of housing policy have been established. It has been clarified that the problem of providing housing historically was initially considered as the problem of an individual person, and only later – one of the issues of the state policy. Such key stages of the development of housing policy as the initiation of housing policy in the ХІХ century, the development of housing policy after the First and Second World Wars, modern challenges of housing policy have been analyzed. It has been emphasized that international standards and recommendations for the formation of housing policy were formed at the beginning of the ХХ century. It has been established that there was a large-scale reconstruction of the housing stock and the construction of typical multi-apartment buildings after the end of the Second World War. It has been emphasized that Ukraine's housing policy after obtaining independence in 1991 had undergone significant changes. It was confirmed by the massive privatization of housing by Ukrainian citizens and the growth of the share of the private housing stock. The authors have offered own periodization of the stages for the formation and development of housing policy in Ukraine, starting from the ХІХ century and up to nowadays. The importance of the historical approach for further development of housing policy, taking into account economic, social and political aspects, has been emphasized.